Diversidade e esfera pública: um debate sobre reconhecimento no interior da teoria crítica. - Mariana Prandini Fraga Assis (2007)
Two fundamental theoretical standpoints, liberalism and communitarianism, have become especially relevant in contemporary debates that center upon the question of how to deal with claims from groups who demand public recognition of their specific characteristics. This work aims at pointing out a third perspective in this debate, commonly called the critical theory of recognition, which has its firm grounding in the theoretical tradition initiated by the scholars of The Frankfurt School. A distinct analytic path is traced with particularemphasis on the contributions of Habermas, Honneth and Fraser. The central objective is to discover, among these contributions, various ways of connecting diversity and the public sphere. First, the work points how the concept of the public sphere, developed in Habermas work, was fundamental for the revitalization of the emancipatory potential of democracy. Nevertheless, it is in his writings that one finds the origin of great concern either for the inclusion or the treatment of diversity/difference in this space. Second, it is analyzed howHonneth, as a follower of critical theorys tradition, discusses the sociological deficit in Habermas theory and with his amplified notion of recognition seeks to shed some light on social conflicts until now, largely invisible. In doing so, he abandons the centrality that the element public sphere had in critical theory, and thus, establishes a very weak relationship between recognition and his excessively limited concept of the public. Lastly, it is showed how Fraser, due in great part to being a critic of the bourgeois model of the public sphere, iscapable of establishing a clear and strong connection between the two elements in her discussions regarding recognition. The notion of parity of participation, given her concerns, demands that difference/diversity, as part of the public sphere, does not convert itself into a source of inequality or impairments to participation. Being that the central question of thiswork is the problem of establishing a positive connection between diversity/difference, recognition and public sphere, Frasers theory appears as the one which best treats the claims for recognition as a public concern.